Obesity and the Odds of Weight Gain following Androgen Deprivation Therapy for Prostate Cancer. (22nd April 2014) - Braunstein, Lior Z.; Chen, Ming-Hui; Loffredo, Marian; Kantoff, Philip W.; D'Amico, Anthony V.
Abstract : Background . Increasing body mass index (BMI) is associated with increased risk of mortality; however, quantifying weight gain in men undergoing androgen deprivation therapy (ADT) for prostate cancer (PC) remains unexplored. Methods . Between 1995 and 2001, 206 men were enrolled in a randomized trial evaluating the survival difference of adding 6 months of ADT to radiation therapy (RT). BMI measurements were available in 171 men comprising the study cohort. The primary endpoint was weight gain of ≥10 lbs by 6-month followup. Logistic regression analysis was performed to assess whether baseline BMI or treatment received was associated with this endpoint adjusting for known prognostic factors. Results . By the 6-month followup, 12 men gained ≥10 lbs, of which 10 (83%) received RT + ADT and, of these, 7 (70%) were obese at randomization. Men treated with RT as compared to RT + ADT were less likely to gain ≥10 lbs (adjusted odds ratio (AOR): 0.18 [95% CI: 0.04–0.89]; P = 0.04 ), whereas this risk increased with increasing BMI (AOR: 1.15 [95% CI: 1.01–1.31]; P = 0.04 ). Conclusions . Consideration should be given to avoid ADT in obese men with low- or favorable-intermediate risk PC where improved cancer control has not been observed, but shortened life expectancy from weight gain is expected.